CORPORATE RESCUE CULTURE: REALITIES AND LIMITATIONS OF THE EXISTING LAWS OF THE UNITED KINGDOM - Khokhar, Farqaleet; Javed, Kashif; Rizvi, Aatir; Ramzan, Dr. Muhammad (The journal of contemporary issues in business and government, 2022)
Two choices are available to a corporation when it is in financial distress. These choices are either to rescue or to terminate the coiporate body. This piece discusses the main procedure of corporate rescue which is administration. The Cork Report 1982 has structured the legal regime on insolvency more specifically, founding the grounds for a corporate rescue culture. The main issue of discussion is whether or not the culture of coiporate rescue has been nourished since the Cork Report with regards to the administration in the light of the Enteiprise Act 2002 despite that there is occasionally an apparent assumption in favour of the presence of a coiporate rescue culture in the jurisdiction of the United Kingdom. This piece scrutinizes the policy issues and practical features of the coiporate rescue, administration management complexities, and moratoria implications. The article further inspects institutional concerns and pinpoints the inconsistencies in the judicial attitude of the UK. The article also provides a comparative perspective highlighting that the United Kingdom can leam the lesson for improvements of its existing laws from the United States although several Achilles heels exist in the United States laws.